If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7(x+1)-3x=3(x-4)+20
We move all terms to the left:
7(x+1)-3x-(3(x-4)+20)=0
We add all the numbers together, and all the variables
-3x+7(x+1)-(3(x-4)+20)=0
We multiply parentheses
-3x+7x-(3(x-4)+20)+7=0
We calculate terms in parentheses: -(3(x-4)+20), so:We add all the numbers together, and all the variables
3(x-4)+20
We multiply parentheses
3x-12+20
We add all the numbers together, and all the variables
3x+8
Back to the equation:
-(3x+8)
4x-(3x+8)+7=0
We get rid of parentheses
4x-3x-8+7=0
We add all the numbers together, and all the variables
x-1=0
We move all terms containing x to the left, all other terms to the right
x=1
| 4x–2=22–8x | | 7/9=6/b-10 | | -x/6=4-(-2) | | 3/7x=2/7x+5 | | 2+4(x+3)=6 | | 2n-n/5=5 | | F(-7)=2x-9 | | 4/5y=—2 | | x2+16x+4=0 | | 3x-9+4=-30 | | 37=u6 | | 9c-18=7c | | 5u-35=10u-80 | | 8-x=3x-3-8x | | 0=-3p+4p | | -4/7k=28 | | c=4c-84 | | 3x-10=3-2x | | 32b+5=20−b | | x/7=—8 | | 11=n/9+1 | | -7k=-9–6k | | 6(x+3)+4=-14 | | 2t-84=t-31 | | 2x+9=9x-11 | | -15c+20=-20–20–20c | | 15/21=20/x | | -w+6=-2w | | x+2-5=-2 | | 5(10-2x)=70 | | 2t–84=t-31 | | 6x+5+2x+5=180 |